Alkaline trypsin from the viscera and heads of Engraulis anchoita : partial purification and characterization - Daniela L. Lamas; Maria I. Yeannes; Agueda E. Massa (BioTechnologia, 2017)
Marine by-products contain valuable protein fractions. To ensure a profitable utilization of wastes from the fish industry, the knowledge about their quality and composition is necessary. Fish digestive proteolytic enzymes from cold-adapted ectothermic organisms have found applications in several industries because their temperature requirements and other characteristics differ from those of homologous proteases from warm-blooded animals. Herein, we describe detection, partial purification, and characterization of proteolytic enzymes from the viscera and heads of Engraulis anchoita. Enzymatic activities of the by-products were assayed using azocaseín as a substrate. To characterize the alkali protein fraction, the activity against inhibitors and their molecular weights were studied. The crude protein extract exhibited maximal activity at pH 8.0 and 60EC. Results relative to the substrate-specific Nabenzoyl-DL-arginine-p-nitroanilide and the 25 kDa molecular weight indicated that the recovered protease was trypsin. The activity showed an increment in presence of SDS and a slight decrease when it was incubated with EDTA. Increasing the concentration of NaCl up to 5% did not significantly decrease the protein’s activity. The results obtained suggest that by-products of anchovy industry could be used in the detergents industry.